Potential Therapeutic Effect and Mechanisms of Mesenchymal Stem Cells-Extracellular Vesicles in Renal Fibrosis - Liao, Chunling; Chen, Guangyong; Yang, Qian; Liu, Yiping; Zhou, Tianbiao (Frontiers in Cell and Developmental Biology, 2022)
Chronic kidney disease (CKD) is one of the most common diseases that endanger human health and life. Its important intermediate link and final pathological manifestation is renal fibrosis (RF). Mesenchymal stem cells (MSCs) have been found to be able to treat organ fibrosis including RF to some extent, but they have some safety problems, such as cell rejection, carcinogenicity, virus contamination and so on, which limit the application of MSCs. However, current studies have found that MSCs may exert their therapeutic effect by releasing extracellular vesicles (EVs). MSC-EV can transfer functional proteins and genetic material directly to the recipient cells. As a non-cell membrane structure, MSC-EV has the advantages of low immunogenicity, easy preservation and artificial modification, but does not have the characteristics of self-replication, ectopic differentiation and so on. Therefore, it is safer and more effective than MSC in treatment. Recent studies have also found that MSC-EV can significantly improve renal function and pathological changes of RF. Thus, this review summarizes the therapeutic effect of MSC-EVs on RF and their mechanisms that have been discovered so far, so as to provide a theoretical basis for the further study of specific components in MSC-EVs that play a key therapeutic role.